Information security in data exchange between mobile devices with Android system using RSA encryption - Solís, Fernando; Pinto, Diego; Solís, Santiago (Enfoque UTE, 2017)
The new styles and ways of life lead to greater use of wireless networks, the mobile device being a tool for data transmission, which are susceptible to threats in the transmission channels in the network. IT security plays a very important role in guaranteeing the availability, privacy and integrity of information, one of the techniques that helps in this task is cryptography, whose foundation is to transform a message so that it is unintelligible except for those who have the Key to decipher it. The research focuses on the use of the RSA algorithm between mobile devices, the encrypted data is sent through communication channels called threads that through formulas and processes executed on the server, will help to execute the encryption and decryption of the data. To carry it out, a prototype for the exchange of data between mobile devices wirelessly was designed and implemented, conducting performance tests with three nodes to improve the security. The results show the efficiency of the algorithm and additionally its functionality, the times of encryption and decryption are fast against the sending of information without any method or algorithm used.